Cloud Based Virtual Machine Allocation Techniques: A Survey - Gomathimari, N; Geetha, N (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing is an ocean of resources which are shared among multiple users for processing over the internet by cloud services like software, infrastructure and platform oriented. Based on the user requests, various processes such as allocation, computation, execution are performed in the cloud environment. An allocation is the most challenging process in the cloud environment. Virtualization technology is the main technology provided by the cloud that is used for that processes. Virtual machines are used for allocating the resources according to the user request. Many algorithms and techniques are used for virtual machine allocation in the cloud environment. In this paper we provide an overview of the fundamental theories and emerging techniques for cloud based virtual machine allocation process as well as several extended work in these areas. This writing provides a research on the cloud based virtual machine allocation techniques that are frequently used in the early work in cloud environment.